(untitled) - Timoshenko, Stephen (New York, 1965)
This is a book that every civil engineer needs as part of their library. After having studied structures about 25 years ago and with computer programs of today it is still an important book where fundamental concepts are derived and applied by hand. It is truely a classical text on structural analysis written by a pioneer and mechanics expert.
Keywords: Structural analysis (Engineering),Phân tích cấu trúc (Kỹ thuật)